Antioxidant activity of mengkudu fruit juice (Morinda citrifolia) and the role as an inhibitor of advanced glycation and products (AGES) by glycosilation reaction - Eko Suhartono Eko Suhartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Mengkudu is a traditional plant with active compound that has antioxidant activity. Diabetes mellitus complication has causative link with AGEs formation that involves free radical. Objective: To know antioxidant activity of mengkudu and the role to inhibit AGEs formation. Methods: This experiment used pre and post test control group design. Antioxidant activity was deter-mined'by reacting the mengkudu juice with 2,4 dinitrophenylhydrazin (DNPH) and analyzed with spectro-photometer a.=390 nm. AGEs absorbancy was measured every 48 hours until 20 days with spectropho-tometer ?=340 nm. Dicarbonyl level was determined with DNPH method that was developed by Uchida and modified by Sadikin.Result: Antioxidant activity of 0.25 g/ml mengkudu juice (Morinda citrifolia) was 125.46±27.79%.Beside that, mengkudu juice can inhibit advanced glycation end products (AGEs) formation.Conclusion: Mengkudu juice can decrease AGEs formation and has antioxidant activity. Key words: antioxidant - mengkudu juice - AGEs - glycosilation